Using transcriptomics, proteomics and phosphoproteomics as new approach methodology (NAM) to define biological responses for chemical safety assessment. (February 2023) - Li, Yuan; Zhang, Zhenpeng; Jiang, Songhao; Xu, Feng; Tulum, Liz; Li, Kaixuan; Liu, Shu; Li, Suzhen; Chang, Lei; Liddell, Mark; Tu, Fengjuan; Gu, Xuelan; et al.
Abstract: Omic-based technologies are of particular interest and importance for hazard identification and health risk characterization of chemicals. Their application in the new approach methodologies (NAMs) anchored on cellular toxicity pathways is based on the premise that any apical health endpoint change must be underpinned by some alterations at the omic levels. In the present study we examined the cellular responses to two chemicals, caffeine and coumarin, by generating and integrating multi-omic data from multi-dose and multi-time point transcriptomic, proteomic and phosphoproteomic experiments. We showed that the methodology presented here was able to capture the complete chain of events from the first chemical-induced changes at the phosphoproteome level, to changes in gene expression, and lastly to changes in protein abundance, each with vastly different points of departure (PODs). In HepG2 cells we found that the metabolism of lipids and general cellular stress response to be the dominant biological processes in response to caffeine and coumarin exposure, respectively. The phosphoproteomic changes were detected early in time, at very low doses and provided a fast, adaptive cellular response to chemical exposure with 7-37-fold lower points of departure comparing to the transcriptomics. Changes in protein abundance were found much less frequently than transcriptomic changes. While challenges remain, our study provides strong and novel evidence supporting the notion that these three omic technologies can be used in an integrated manner to facilitate a more complete understanding of pathway perturbations and POD determinations for risk assessment of chemical exposures. Graphical abstract: Image 1 Highlights: First in-depth study that measures multi-omics effects induced by chemicals. Using NAMs are able to capture the complete chain of events induced by chemicals. Tiered phosphoproteomic, transcriptomic, and proteomic response to chemicals. Phosphoproteome provided a fast, adaptive cellular response to chemical exposure. The points of departure calculated by phosphoproteomics were 7-37-fold lower comparing to the transcriptomics.